2001
DOI: 10.1073/pnas.101129798
|View full text |Cite
|
Sign up to set email alerts
|

Large carbon isotope fractionation associated with oxidation of methyl halides by methylotrophic bacteria

Abstract: The largest biological fractionations of stable carbon isotopes observed in nature occur during production of methane by methanogenic archaea. These fractionations result in substantial (as much as Ϸ70‰) shifts in ␦ 13 C relative to the initial substrate. We now report that a stable carbon isotopic fractionation of comparable magnitude (up to 70‰) occurs during oxidation of methyl halides by methylotrophic bacteria. We have demonstrated biological fractionation with whole cells of three methylotrophs (strain I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 36 publications
4
55
4
Order By: Relevance
“…Recent work by Miller et al (2001 and has shown a KIE of 1.045 and 1.049, respectively, for degradation of CH 3 Cl by soil bacteria. Thus a microbial sink accounting for around 20-30% of atmospheric CH 3 Cl significantly affects the δ 13 C value of atmospheric CH 3 Cl.…”
Section: Kinetic Isotope Effects Associated With Known Sinks For Tropmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Miller et al (2001 and has shown a KIE of 1.045 and 1.049, respectively, for degradation of CH 3 Cl by soil bacteria. Thus a microbial sink accounting for around 20-30% of atmospheric CH 3 Cl significantly affects the δ 13 C value of atmospheric CH 3 Cl.…”
Section: Kinetic Isotope Effects Associated With Known Sinks For Tropmentioning
confidence: 99%
“…Another sink for atmospheric CH 3 Cl, is degradation by soil microorganisms for which Montzka and Fraser Montzka and Fraser (2003), except for the value shown in brackets for the sink (best estimate) for microbial degradation in soil which is from that suggested by and discussion in the text of this manuscript. b Gola et al (2005) c Thompson et al (2002) and discussion in this manuscript d mean of Miller et al (2001Miller et al ( , 2004 ? denotes that no value has been provided (2003) gave a best estimate of 180 Gg yr −1 .…”
Section: Introductionmentioning
confidence: 99%
“…If the same bond is broken in the same way, then a similar intrinsic isotope effect can be expected; however, this value may again be masked by slow nonfractionating preceding processes. For example, for the degradation of methylbromide by the bacterial strain CC495 (77), the small AKIEC obtained may be due to partly rate-limiting step(s) preceding the transformation of the compound. The low values obtained with assays of isolated enzyme in the case of methyl chloride suggest that it is not only the transfer through the cell membrane that may be rate-limiting but that also an elevated commitment to catalysis (e.g., secondary slow steps in the actual enzyme reaction) occurred.…”
Section: Evaluation Of Published Isotope Fractionation Data In Terms mentioning
confidence: 99%
“…Further, it is known that enzymatic dehalogenation reactions impart a particular chlorine KIE on various organochlorine compounds (e.g., Numata et al 2002;Paneth 2003). For atmospheric systems, isotope studies have been largely confined to a few elements, especially C and H (e.g., Bill et al 2002;Brenninkmeijer et al 2003;Keppler et al 2004Keppler et al , 2005McCauley et al 1999;Miller et al 2001;Saito and Yokouchi 2008). The use of multiple isotope systems might allow the source or sources of a particular sample of, for instance, methyl bromide to be ascertained with greater certainty.…”
Section: Introductionmentioning
confidence: 99%